Chemical Twinning of Salt and Metal in the Subnitridometalates Ba23Na11(MN4)4 with M=V, Nb, Ta. Issue 36 (3rd August 2016) - Wörsching, Matthias; Tambornino, Frank; Datz, Stefan; Hoch, Constantin
Abstract: The subnitridometalates Ba23 Na11 (MN4 )4 (M=V, Nb, Ta) crystallize in a new structure type, which shows ionic ortho ‐nitridometalate anions and motifs from simple (inter)metallic packings: Na‐centered [Na8 ] cubes as cutouts of the bcc structure of elemental Na and Na‐centered [Ba10 Na2 ] icosahedra as found in Laves phases, for example. Single‐crystal and powder X‐ray diffraction studies in combination with quantum‐chemical calculations of the electronic structure and Raman spectroscopy support the characterization of the subnitridometalates as "chemical twins". They consist of independent building units with locally prevalent ionic or metallic bonding in an overall metallic compound. Abstract : Chemical twins : The subnitridometalates Ba23 Na11 (MN4 )4 (M=V, Nb, or Ta) can be described as "chemical twins" with separated ionic and metallic motifs. The chemistry of the subnitrides was thus extended through the incorporation of complex nitridometalate anions into a metallic matrix of barium and sodium atoms.